Optimization of the Use of Kurisi Fish Flour (Nemipterus japonicus) in Fettuccine to Increase Protein Content - Salsabila Putri Denita; Rifki Prayoga Aditia; Devi Faustine Elvina Nuryadin (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2026)
The optimization of the utilization of kurisi fish flour (Nemipterus japonicus) in fettuccine aims to enhance nutritional content through protein fortification and evaluate the characteristics and sensory properties of the product. The research was conducted at the Aquatic Product Processing Technology Laboratory, Sultan Ageng Tirtayasa University, using a Completely Randomized Design with four treatments of fish meal concentration (P0 = 0%; P1 = 20%; P2 = 25%; P3 = 30%) and two replications. The analysis of fettuccine includes proximate analysis, sensory analysis, and physical analysis. The research results show that the addition of kurisi fish flour to fettuccine can improve the nutritional content of the product, with a protein content reaching 16.49%. However, the addition of kurisi fish flour in excessively high percentages can decrease the panelists' preference because it produces a more dominant fish taste and aroma in the sensory analysis. Therefore, the addition of kurisi fish flour needs to be optimized so that the increase in nutritional content aligns with the sensory acceptance of the product.